Follow-up phone calls increase nutrient intake estimated by three-day food diaries in 13 year old participatns of the Raine study. - Candilo, K.; Oddy, Wendy; Miller, M.; Sloan, N.; Kendall, Garth; Klerk, N. (Union Offset Printers, 2007)
Our primary objective was to determine the effect of follup up phone calls on estimated nurtrient intakes obtained by three day food diaries from 13 year old adolescents. Food diaries were recorded using household measures and entered into a dietary analysis software program before and after follow up by telephone. A sample of 340 participatns aged 13 years born in to the WA Pregnancy Cohort (Raine) study, a population-based longitudinal cohort followed from 16 to 20 weeks gestation to 13 years of age. After face to face instruction, participants completed three day food diaries at home and returned them by post. Follow uptelephone calls were ade to each participant to improve data collection response and to verify missing details in the food diaries. Nutrient intakes before and after telephone follow up were compared using Student's t-tests in SPSS. Results were also compared with those of the Child and Adolescent Physical Acitivy and Nutrition Survey.Follow up phone calls significantly inceased the estimated intake of total kilojouules, water, total carbohydrates, sugars and magnesium (p<.005).These results indicate the importance of follow up phone calls to obtain missing detials in three day food diaries completed by adolescents.